The Diversity Of Grasshoppers (Subordo Caelifera) In The National Park Of Mount Merbabu And Mount Pangonan Central Java - Nursin, Lili Shafdila; Sulistiyawati (Proceeding International Conference on Science and Engineering, 2021)
Abstract. This study aims to determine the diversity of grasshoppers in the National Parks of Mount Merbabu and Mount Pangonan. The research method used is the exploration method and purposive sampling. The results of research on grasshoppers in the National Park of Mount Merbabu and Mount Pangonan, respectively, were shannon-wiener index diversity (H '= 2.187 and H' = 1.089), number of individuals (N = 92 and N = 35), and species evenness index (E = 0.697 and E = 0.608). The grasshoppers species found were Phlaeoba fumosa, Phlaeoba infumata, Phlaeoba sp. 1, Phlaeoba sp. 2, Phlaeoba sp. 3, Phlaeoba sp. 4, Phlaeoba sp. 5, Phlaeoba sp. 6, Caryanda spuria, Cercinae sp., Chitaura sp., Oxya sp., Erucius sp. 1, Erucius sp. 2, Atractomorpha crenulata, Atractomorpha sp. 1, Atractomorpha sp. 2, Atractomorpha sp. 3, Atractomorpha sp. 4, Atractomorpha sp. 5, Atractomorpha sp. 6, Atractomorpha sp. 7, Tettigidea lateralis, and Tettigidea sp.